2017
DOI: 10.1002/sctm.16-0335
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Secretase Inhibitor IX (GSI) Impairs Concomitant Activation of Notch and Wnt-Beta-Catenin Pathways in CD44+ Gastric Cancer Stem Cells

Abstract: Cancer stem cells (CSC) are associated with tumor resistance and are characterized in gastric cancer (GC). Studies have indicated that Notch and wnt‐beta‐catenin pathways are crucial for CSC development. Using CD44+ CSCs, we investigated the role of these pathways in GC carcinogenesis. We performed cell proliferation, wound healing, invasion, tumorsphere, and apoptosis assays. Immunoblot analysis of downstream signaling targets of Notch and wnt‐beta‐catenin were tested after gamma‐secretase inhibitor IX (GSI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Our study also revealed that PS1 plays an important role in CD44s-mediated EMT induction. Therefore, in addition to confirming previous studies showing that gamma-secretase inhibitors are effective in inhibiting CSC properties via suppression of Notch activity [ 28 , 29 ], the present results point to the existence of another mechanism mediating the suppressive effects of gamma-secretase on CSCs. Combination treatment using CDDP and gamma-secretase inhibitors might be a useful approach in overcoming the resistance of several types of cancers to chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…Our study also revealed that PS1 plays an important role in CD44s-mediated EMT induction. Therefore, in addition to confirming previous studies showing that gamma-secretase inhibitors are effective in inhibiting CSC properties via suppression of Notch activity [ 28 , 29 ], the present results point to the existence of another mechanism mediating the suppressive effects of gamma-secretase on CSCs. Combination treatment using CDDP and gamma-secretase inhibitors might be a useful approach in overcoming the resistance of several types of cancers to chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported CSCs to be involved in the stepwise progression of solid tumors including breast, gastric, and cervical cancer . CD44 and activation of WNT, NOTCH1 increases aggressiveness, correlating with progression in colon cancer . CD133 is also associated with enrichment of undifferentiated cells and tumorigenic behavior along with its implication in epithelial dedifferentiation .…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of Notch receptors using Numb, an endogenous inhibitor of Notch receptors in CD133 + CD24 + renal cell carcinoma CSCs, led to a reduction in self-renewal and drug resistance in these CSCs [136]. Treatment with gamma-secretase inhibitor IX (GSI), a Notch inhibitor, inhibited proliferation and induced apoptosis in CD44 + gastric CSCs [137]. These studies collectively suggest the importance of Notch signaling in the maintenance of stemness in CSCs.…”
Section: Maintenance Of “Cancer Stemness”mentioning
confidence: 99%